REFERENSI ENDOFORA DALAM KUMPULAN CERPEN KARPET MEREH WAKIL PRESIDEN KARYA ABDUL KADIR IBRAHIM - Ayu Riski; Auzar Auzar; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: This study discussed the endofora reference in short stories collections of Karpet Merah Wakil Presiden of Abdul Kadifr Ibrahim work. In general, the problem studied in this study is about the type of endofora reference based on the direction and type of object in short stories collections of Karpet Merah Wakil Presiden of Abdul Kadir Ibrahim work. The method used in this study was descriptive method with qualitative approach, which is the data in the form of a series of text that get realization of endofora reference. The techniques used in this study were documentation and record techniques. The data source of this study was obtained directly from the book short stories collections of Karpet Merah Wakil Presiden of Abdul Kadir Ibrahim works. The result of this study indicate there are 417 endofora references data. The overall data consists of 284 personal reference data of anaphora category, 67 personal reference data of kataphora category, 5 demonstrative reference data of anaphora category, 7 demonstrative reference data of the kataphora category, 4 comparative reference data of anaphora category, and 4 comparative reference data of kataphora category.Keyword : endofora reference, type of endofora reference, short stories collections